Perception and awareness of first year MBBS students about the subject community medicine - Gupta, Sunanda; Kishore, Jugal (International Journal Of Community Medicine And Public Health, 2022)
Background: In India, departments of the medical discipline community medicine or preventive and social medicine began to be established in the year 1955. It plays important role in medical curriculum for imparting training as comprehensive healthcare giver at various levels of health system. This study aimed at assessing perception and awareness of first year MBBS students about the subject community medicine, before formal introduction of the discipline as a part of their medical curriculum. Methods: The cross-sectional study was conducted in a class of seventy-four students of first year MBBS, at Vardhman Mahavir Medical College and Safdarjung Hospital, Delhi, in May 2022. Results: One-third of students had either parent/sibling/close relative as doctor. One-third of students knew at least one person who had pursued the discipline ‘community medicine’. Most of the students (85%) expected to learn healthcare management at primary healthcare level from the medical discipline. Only one-third of the students were aware of the subject before joining MBBS. Students whose parent/sibling/close relative is doctor, differed significantly about having the knowledge about the discipline before admission to MBBS (p value <0.001). Also, students who knew any person who had pursued community medicine as specialization, had significantly more chance of knowing about the subject before admission to MBBS. Conclusions: The medical discipline of community medicine is yet to gain familiarity among students. Community medicine specialists should come forward to address the issue and popularize the discipline as a component of medical curriculum and highlight their role in front of general population as well.